Захист інформації з інтелектуальною підтримкою організаційно-технічного й оперативного управління - Толюпа, С. В.; Пархоменко, І. І. (Видавництво Львівської політехніки, 2016)
Для успішного використання сучасних інформаційних технологій необхідно ефективно управляти не тільки мережею, але і її системою захисту інформації (СЗІ), при цьому на рівні інформаційної системи автономно повинна працювати система, яка реалізує управління складом подій інформаційної безпеки, планування модульного складу СЗІ й аудиту. З огляду на те, що СЗІ є доволі складною організаційно-технічною системою, що функціонує в умовах невизначеності, суперечливості та неповноти знань про стан інформаційного середовища, управління такою системою має ґрунтуватися на застосуванні методів теорії прийняття рішень і необхідності застосування інтелектуальних технологій. For the successful use of modern information technologies, it is necessary to effectively manage not only the network, but also information systems security (ISS), the information system on the level of the system must operate autonomously implementing the management structure of information security events, planning the composition of modular ISS and audit. ISS is a very complex organizational and technical system, which works under conditions of uncertainty, inconsistency and incompleteness of knowledge about the state of the information environment, the management of such system should be based on the use of methods of the theory of decision-making and the need for the use of intelligent technologies. One solution to this problem is to use the intelligent methods to support decision-making in the management of IS local information system, which, in turn, requires the development based on the principles of system analysis and general scientific approaches methodological framework for the protection of information management, the relevant models, methods, algorithms and software. The circuit of organizational and technical management are mechanisms to protect the information management infrastructure with changing business applications, information processing plans and corresponding to the level of data protection requirements. The circuit includes: intelligent decision support for the choice of strategies to protect system security level evaluation system (risk) control action is implemented by employees of information security department. The command information is generated during the planning - targeted selection of a rational complex remedies. Formed operational command information that is communicated to the security administrator control object or automatically by means of implementing control actions on the built-in protection circuit control modules in the operational management. The proposed structure of building intellectual support system of operational management can be built by this principle. By development of the intellectual system of operative management it is suggested to choose an unclear model. It is related to that considerable part of information about reasons and sources of anomalous events can be got only an expert way or as heuristic descriptions of processes. For determination of sources of АP IS must be presented by the model of that informative network to that she is oriented. This model divides the task of moving to information between computers through the environment of network on the amount of levels of less large and easier solvable small tasks. Each of these small tasks decides by means of one network level. Thus it can be argued that the methodological basis of the information security management in the segment of the local information system, based on system analysis and general laws of building management systems, the novelty of which lies in the totality of the developed methods, principles of building architecture information security management system with intelligent support for organizational and technical and operational management, which allows a rapid and informed decisions to ensure the required level of data protection.
Keywords: захист; системний аналіз; система; інформація; інформаційна безпека; загроза; локальна мережа; урівень захищеності